'The independence of Belgium is forfeited.' Narratives of legitimation in the annexation debates of the German war public, 1914–1918. Issue 2 (3rd May 2020) - Bischoff, Sebastian
ABSTRACT: Early in the war, anti-Belgian ideas were already occupying a central place among the German public's images of the enemy. These were created within a very short time frame and drew upon stories of the alleged bestial expulsions of German nationals by Belgian citizens, supposedly organized by the state authorities and the purportedly cruel warfare conducted by Belgian civilians against German troops. At the same time, the question of Belgian neutrality arose and the German concession that this had been breached out of self-defence was rescinded. Thus emerged discursive images of Belgians and Belgium which depicted new character traits of its western neighbour's population and which ultimately formed the basis for the entire wartime discussion of potential German control of the country. Based on a broad corpus of sources, this article examines the rhetoric and dynamics of the 'annexation debates' in Germany's public sphere, while focusing on the underlying concepts of order in Belgium and also portrays the critical voices in these debates.